Transformasi Pembelajaran Shalat Bagi Anak Berkebutuhan Khusus: Pendekatan Inklusif dalam Pendidikan Islam Kontemporer - Ririn Lailatul Masykuro; Syuhud (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2026)
Inclusive education demands equality of spiritual access, yet prayer learning for Children with Special Needs (CSEN) often still neglects pedagogical design that is responsive to the diversity of students' capacities. This study aims to analyze the implementation of prayer learning transformation for CSEN through an inclusive approach, as well as its challenges and relevance to contemporary Islamic education values. The research method uses an instrumental qualitative case study at SLB Bhakti Wanita Lumajang. Data were collected through participatory observation, in-depth interviews, and document analysis, then processed using an interactive analysis model. The results show that the transformation of prayer learning was successfully realized through differential pedagogical adaptation, non-discriminatory personal assistance, and the creation of an accessible worship ecosystem in the school environment. Despite limitations in adaptive media and teacher competence, the application of multimodal strategies and process-based assessment proved effective in sustainably improving understanding, spiritual motivation, and consistency of worship practice. These findings affirm that worship inclusivity is a real manifestation of maqashid syariah and the principle of rahmatan lil 'alamin. This research fills an empirical gap in Islamic education literature that still lacks structured discussion on the implementation of inclusive prayer learning, offering novelty through the integration of multimodal strategies and process-based assessment that operationally translates the principles of maqashid syariah and rahmatan lil 'alamin into pedagogical practices in schools.